The Diversity and Abundance of Planktonic Diatoms Vertically in Nareh Coastal Waters Manggung Village North Pariaman Sub-District Pariaman City West Sumatera Province - Prasiska, Yulia; Thamrin, Thamrin; Siregar, Sofyan Husein (Journal of Coastal and Ocean Sciences, 2020)
This research was conducted in March 2020 to find out the difference in planktonic diatoms abundance vertically at each station in the waters of Nareh Beach, Manggung Village, North Pariaman Sub-District, Pariaman City, West Sumatra Province. The method used is a survey method that consists of three depths at three observation stations. The water quality measured in this study were temperature, brightness, pH, salinity, current velocity, and depth. Based on the research results, there are 11 types of planktonic diatoms found in the waters of Nareh Beach, namely Gyrosigma sp., Chaetoceros sp., Odontella sp., Rhizosolenia sp., Pleurosigma sp., Thalassionema sp., Leptocylindrica sp., Coscinodiscus sp., Nitzschia sp., Guinardia sp, and Skeletonema sp. the most dominant one. The highest total value of planktonic diatom abundance ranges (9779.65-12867.96 ind/L) is found in the surface layer and the lowest ranges (2573.59-10294.37 ind/L) is at 5 m depth. There is no difference in the total value of planktonic diatom abundance between depths